Il diritto delle comunità umane intenzionali: nuovi ordinamenti giuridici? - Piliu, Salvatore (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The purpose of this paper is to analyze from a legal standpoint the new, globalized phenomenon of intentional human communities, in order to understand whether these new types of human collectives can be considered as alternative forms of traditional organizational models and capable of creating new legal systems, starting from the assertion ubi societas ibi ius. Basing on the definitions elaborated in the field of legal sociology and intentional communities, we analyzed a intentional community’s capacity to produce legal rules that apply to that members. The legal organization of the Community of Damanhur, located in Piedmont (Italy), where there are internal rules of private and public law regulating the life of its members, is a genuine legal system, which poses many problems in relation to Italian law. The new bill submitted to the Italian Parliament in 2017 on the legal recognition of intentional communities could definitively regulate the relationship between an Intentional Community and the State, with the consequent recognition of the existence of ‘autonomous legal systems’ for all Intentional Communities.